How effectively shape the infrastructure of sustainable development? - Tokarski, Daniel (W poszukiwaniu zielonego ładu, 2022)
The work considers the issue of building an appropriate infrastructure for green business. A conceptual approach to the sustainable development infrastructure was presented along with its classification, elements, shaping criteria and principles conducive to the implementation of pro-ecological strategies. Properly planned activities result in rational shaping of infrastructure investments and the desired level of management of natural resources in the process of restoring the environment to a state of equilibrium.